Identification and characterization of the pathogens causing Fusarium dry rot of potatoes - O. P. Gavrilova; A. S. Orina; T. Yu. Gagkaeva (Аграрная наука Евро-Северо-Востока, 2025)
Based on the results obtained in this study, the taxonomic status of 11 fungal strains belonging to the Fusarium oxysporum species complex isolated from potato tubers with symptoms of Fusarium dry rot collected in three federal districts of the Russian Federation was clarified. The pathogenicity of strains to tubers of three potato cultivars and their sensitivity to fungicides recommended for the protection of this crop were characterized. The phylogenetic analysis of fragments of translation elongation factor (tef) and large subunit of RNA polymerase II (rpb2) genes allowed to identify the analyzed Fusarium strains as representatives of two species – F. oxysporum s. str. (4) and F. nirenbergiae (7). The F. nirenbergiae strains turned out more aggressive to tubers of potato cultivars ‘Gala’, ‘Impala’ and ‘Red Scarlett’ and caused on average 1.3–1.9 times more extensive damage of plant tissue (19.0–41.6 mm) compared to F. oxysporum strains (3.2–34.6 mm), which demonstrated high intraspecific variability in pathogenicity. Characterization of strain’ sensitivity to four fungicides containing active substances from different chemical classes revealed both interspecific and intraspecific differences of fungi. The strains of both species were the most sensitive to the benomyl-containing fungicide, which effectively inhibited fungal growth (EC50 = 0.0003 % on average for each species). The lowest sensitivity of the strains, especially F. oxysporum, was found in relation to the fludioxonil-containing fungicide (EC50 > 1 %).